HUBUNGAN TINGKAT PENGETAHUAN DENGAN KESIAPAN MENGAHADAPI MENARCHE PADA SISWI KELAS V DAN VI SDN 11 NAN SABARIS KABUPATEN PADANG PARIAMAN - MAIFITA, YESI; SAFITRI, WELLIANI (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Knowledge of adolescent girls related to early signs of puberty in the form of menarche (first menstruation) is still low in Padang Pariaman Regency. Meanwhile, adolescent girls should have sufficient knowledge and information to face menarche. The purpose of this study was to determine the relationship between the level of knowledge and readiness to face menarche in grade V and VI students of SDN 11 Nan Sabaris, Padang Pariaman Regency. The method used in this study was descriptive analytical using a cross-sectional approach. The population in this study were 30 grade V and VI students of SDN 11 Nan Sabaris. Sampling was done using the total sampling technique so that the sample size was 30 people. The instrument ini this research was questionnaire. Data processing was computerized with Chi-Square analysis at α = 5%. The results showed that 66.7% of respondents had high knowledge and 70.0% of respondents were ready to face menarche. Bivariate chi square analysis showed that p-value = 0.00 which means there is a significant relationship between the level of knowledge and readiness to face menarche in grade V and VI students of SDN 11 Nan Sabaris (p-value = 0.00 <α = 0.05). The conclusion of this study is that the level of adolescent knowledge in facing menarche in grade V and VI students of Nan Sabaris is related to their readiness.